THE POLITICAL CRITERION FOR EDUCATION? Expansion of public secondary education in São Paulo (1930-1971) - Diniz, Carlos Alberto; Souza-Chaloba, Rosa Fatima de [UNESP] (Univ Fed Sao Paulo, Dept Education, 2023)
This text is an analysis of the political game involved in the creation of secondary schools (high schools) in the state of Sao Paulo from 1930 to 1971. It examines the conflicting trajectory of the expansion of the Sao Paulo public secondary marked by the prevalence of the political criterion between the 1930s and 1950s and the attempts, not always successful, to change this trend in the 1960s, new institutional actors and new patterns of political intervention interposing the rationalized planning of expansion of the school network, especially the performance of the State Education Council and the State Department of Education. The study is based on Political History and the notion of the political field using documentary sources such as the school creation bills, educational legislation and the State Education Plan.
Keywords: History of Secondary Education; Expansion of High Schools; Secondary Education in Sao Paulo